Penguatan Literasi Karier Mahasiswa di Bidang Perbankan melalui Talkshow Kolaboratif Bank Mandiri dan OJK - Niken Probondani Astuti; Wiyana, Anim (LPPM Universitas HKBP Nommensen, 2026)
This community service program aims to enhance students’ career literacy in the banking industry and financial supervisory institutions through a talk show. The activity was attended by 100 active students and featured two speakers from Bank Mandiri and the Financial Services Authority (OJK) of South Sulawesi and West Sulawesi. The methods consisted of preparation, speaker coordination, interactive sessions, and evaluation. The results show that students gained comprehensive insights into recruitment processes, professional ethics, mental readiness, regulatory requirements, and personal branding strategies for entering the financial sector. Moreover, the activity increased students’ motivation and readiness to face job competition. These findings confirm that practitioner-based educational activities are highly effective in strengthening young generations’ career preparedness in the financial industry.